2011
DOI: 10.2478/v10035-011-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Advisability of Palliative Resections in Incurable Advanced Gastric Cancer

Abstract: Effective treatment is the primary objective of surgeon in the treatment of advanced gastric cancer. Poor prognosis and significant advancement of gastric cancer at the time of diagnosis are decisive factors for the only possible surgical management method being palliative procedures. the aim of the study was the evaluation of the value of palliative resection procedures in patients with advanced gastric cancer. Material and methods. The subject in the study was a group of 105 patients with gastric adenocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Our findings suggest that the prognosis of young individuals with advanced or unresectable gastric cancer is worse than that of elderly patients and age is a significant independent factor associated with worse prognosis in patients with unresectable gastric cancer. Our study also found that palliative resection can improve the survival of young patients with incurable gastric cancer ( P = 0.0003) ( 22 , 23 ). Therefore, palliative resection may be considered for advanced and incurable young patients with good basic physical condition.…”
Section: Discussionsupporting
confidence: 68%
“…Our findings suggest that the prognosis of young individuals with advanced or unresectable gastric cancer is worse than that of elderly patients and age is a significant independent factor associated with worse prognosis in patients with unresectable gastric cancer. Our study also found that palliative resection can improve the survival of young patients with incurable gastric cancer ( P = 0.0003) ( 22 , 23 ). Therefore, palliative resection may be considered for advanced and incurable young patients with good basic physical condition.…”
Section: Discussionsupporting
confidence: 68%
“…The non-curative surgery with the intent of symptom palliation, which usually included resectional surgery and non-resectional surgery such as surgical bypass, achieved a narrow range of median OS from 3 to 13 months [18], [29]–[32]. Evidence showed the significantly superior survival prognosis of the non-palliative, non-curative resection than palliative, non-curative resection [12] and palliative bypass [33], [34]. In comparison to many studies with mixed intents, one important reason for this long median OS (28 months) of non-curative surgery group is that we centered on non-palliative, non-curative resections for asymptomatic patients in most recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Median overall survival durations of 8.5-13.8 months have been reported following resectional surgery alone as the principal treatment modality for patients with incurable gastric cancer, 18,25,[53][54][55][56][57] compared with a median overall survival of 13.8 months for patients HER2-positive tumours who received trastuzumab in the TOGA trial. 49 The comparable survival demonstrated for these treatment modalities suggests that an individualized, patient-centred multidisciplinary approach should be advocated, offering either operative or nonoperative treatment after careful risk stratification.…”
Section: Discussionmentioning
confidence: 96%